PENGARUH TEKNOLOGI KEUANGAN DAN KUALITAS LAYANAN DIGITAL TERHADAP KEPUASAN NASABAH PADA BANK SYARIAH INDONESIA KCP MASBAGIK - Vina Yolanda; Riduan Mas’ud; Shofia Mauizotun Hasanah (UIN Mataram, 2022)
This study aims to determine the effect of financial technology and digital service quality at BankSyariah Indonesia KCP Masbagik on customer satisfaction either partially or simultaneously. Andwhat is used in this study is primary data obtained directly from the answers of 100 respondentswho are customers of Bank Syariah Indonesia KCP Masbagik who use digital service facilitiessuch as BSI Mobile, BSI Internet Banking, BSI SMS Banking, and ATM. The analytical methodused is multiple linear regression analysis method. The results show that (1) the significance levelof the financial technology variable (X1) is 0.097, which is smaller than = 0.1. So it can beconcluded that Ho is rejected and Ha is accepted, which means that the financial technologyvariable (X1) has a significant effect on customer satisfaction. (2) the level of significance of thedigital service quality variable (X2) is 0.006 which is smaller than = 0.1. So it can be concludedthat Ho is rejected and Ha is accepted, which means that the digital service quality variable (X2)has a significant effect on customer satisfaction. (3) the acquisition of the Fcount value of 8.789with a Sig value of 0.000. Which hereby indicates that the value of Fcount is greater than thevalue of Ftable and the value of Sig is less than 0.1. It can be concluded that Ho is rejected andHa is accepted. This shows that financial technology and digital service quality together have asignificant influence on customer satisfaction. (4) the value of R2 (R Square) is 0.625 or 62.5%.These results show that the influence of financial technology and digital service quality oncustomer satisfaction is 62.5%. So it can be concluded that the independent variable used in thismodel is able to explain the dependent variable of 62.5%. While the remaining 37.5% isinfluenced by other variables that are not included in this research model